Water column poly-aromatic hydrocarbon anomalies measured with submersible gliders in the Angolan natural oil seepage province. (September 2021) - Jatiault, Romain; Dhont, Damien; Besson, Florent; Tedetti, Marc; Pasqueron de Fommervault, Orens; Loncke, Lies; Bourrin, François; Goutx, Madeleine; Durrieu de Madron, Xavier
Abstract: Fluorescence sensors mounted on unmanned underwater gliders open new ways of investigation to detect dissolved hydrocarbons in seawater. A glider was deployed for 20 days to monitor biogeochemical and physical signals associated with natural hydrocarbon seepages within the first 700 m in the Angolan waters. The glider was equipped with fluorometers (MiniFluo-UV) to measure the concentrations of polycyclic aromatic hydrocarbons (PAH) of interest, i.e. naphthalene, phenanthrene, fluorene and pyrene. A continuous PAH-like signal detected within the 70 m layer below the sea surface is associated with high chlorophyll concentration in the deep chlorophyll maximum. Vertical PAH-like anomalies forming either strong spikes or diffuse columns down to 700 m are observed at the exact location of oil seep sites identified on Synthetic Aperture Radar satellite images. An ~200 m thick layer of enhanced PAH-like concentration, topped by a thermo/pycnocline identified at 280–300 m water depth, is measured in concomitance with the decrease in oxygen concentration. The concomitance of these signals suggests that lower oxygen concentrations induce a preservation of hydrocarbons within the eastern Atlantic oxygen minimum zone. Even if the absence of in-situ measurements limits the understanding of physical and biogeochemical processes affecting PAH concentrations, the measurements conducted at the edges of the OMZ suggests a relationship with microbial activity and organic matter dynamics in this layer. The results presented here show that gliders equipped with PAH sensors represent a promising means for monitoring hydrocarbons in the oceans, especially when they are coupled with other systems (i.e. Synthetic Aperture Radar). Highlights: We combined satellites and an underwater glider to monitor natural hydrocarbon seepage in the Lower Congo basin. The detection performance of an underwater glider is evaluated for the detection of natural oil seeps. Hydrocarbon presence in the water column is well expressed in the pyrene channel as vertical high-amplitude signals. Fluorescence measurements suggest a trapped plume of hydrocarbon in the oxygen minimum zone.